Failed Femicides Among Migrant Survivors - Weil, Shalva (Qualitative Sociology Review, 2016)
Femicide—the killing of a female because of her gender—is becoming an increased object of sociological enquiry, rectifying years of invisibility. The article presents results from ethnographic interviews with three migrant women who survived “failed femicides.” A “failed femicide” is defined as an attempted femicide where the medical examination of the victim confirmed a life-threatening event, the victim had been hospitalized in emergency, and she or the perpetrator had described the event as an attempted murder. It is argued that failed femicides should be added to the growing literature on domestic violence, on the one hand, and femicide, on the other. The article presents narratives from three survivors of failed femicide attempts among Ethiopian female migrants in Israel. They present an interesting contrast to large-scale, quantitative, ethnocentric, male-oriented studies of femicide focusing on Western women. Since few women actually survive femicide attempts, the nature of the small sample should not deter the scholar from the depth of migrant women’s plights. The survivor narratives were analyzed by means of thematic analysis. The analysis produced five key categories: village society in Ethiopia; cycle of domestic violence; motive; weapon; and recourse to authorities. The themes provided understanding into these migrant women’s subjective experiences and the ways they understood events. While no generalizations can be made, the article may encourage comparisons with other failed femicide survivor narratives from other migrant women originating and residing in different settings. With the increase of migrants the world over, non-Western survivor narratives may become an increasingly important tool for policy-makers and for academics to understand how femicides occur, how migrant women perceive them, and how they can be combated.